Strategi Pembelajaran PAI dalam Pembentukan Karakter dan Akhlak Generasi Alpha di MTs Ma’arif NU Sragi Pekalongan - Faris Azzam Husain; Nur Kamaluddin akhmad; Mohammad Syaifuddin (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
The learning strategy of Islamic Religious Education (PAI) plays a crucial role in shaping students' character and morality, especially in addressing educational challenges in the era of Generation Alpha. This generation, born amid rapid technological advancement, tends to be fast-thinking, visual, and practical, yet is also vulnerable to moral crises and ethical degradation. This study aims to describe and analyze the PAI learning strategies implemented at MTs Ma’arif NU Sragi in shaping the noble character and morals of students. The research employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The findings reveal that the applied learning strategies include project-based religious learning, internalization of values through teacher role modeling, utilization of Islamic digital media, and contextual learning relevant to students' daily lives. These strategies have proven effective in instilling values of religiosity, discipline, responsibility, and honesty. The success of these strategies is supported by a religious school environment, active teacher involvement, and parental support. Challenges encountered include limited technological facilities and the pervasive negative influence of social media. This study recommends the reinforcement of collaboration among teachers, parents, and educational institutions to optimize the role of PAI in developing the character of future generations.